Monotonic and cyclic behaviors of loose anisotropically consolidated calcareous sand in torsional shear tests. Issue 4 (21st April 2019) - Zhou, Xiao-Zhi; Chen, Yu-Min; Li, Wen-Wen; Liu, Han-Long
ABSTRACT: The behavior of loose anisotropically consolidated calcareous sand obtained from an island in the South China Sea was investigated under undrained monotonic and cyclic loading in a hollow cylinder torsional apparatus. The tests were conducted on specimens which consolidated under various initial effective confining pressures and consolidation stress ratios. The monotonic test results show that the failure and phase transformation line are essentially independent of the consolidation conditions, while the initial contractive tendency of the specimens decreases with an increasing consolidation stress ratio. During monotonic loading of the anisotropically consolidated specimens, a same major principal stress direction is observed at the constant stress ratio lines up to the phase transformation line, irrespective of initial effective confining pressure. The cyclic strength of the sand increases with an increasing consolidation stress ratio. Moreover, a pronounced stress dependence is observed in the sand with higher consolidation stress ratio. During cyclic loading, the generated excess pore water pressure presents considerable fluctuations. The normalized terminal excess pore water pressure is described as a function of consolidation stress ratio. The tests show that the particle shape, rather than particle crushing, plays an important role in the monotonic and cyclic behaviors of the calcareous sand.